ANALISIS SEMIOTIKA MENGENAI KESENJANGAN SOSIAL PADA FILM PARASITE KARYA BONG JOON HO - Merrisa Alexandra; Dian Rinjani (JURNAL PURNAMA BERAZAM, 2022)
The South Korean film Parasite directed by Bong Joon-ho in 2019 managed to captivate many viewers. Bong Joon-ho wants to reveal the life between the rich and the poor through this film. Some of the scenes shown, in fact, have many meanings about social inequality. However, Bong Joon-ho portrayed it through symbols. This research will be analyzed using Pierce's semiotic theory. Therefore, this study aims to prove the meaning of social inequality contained in several scenes in the film by using semiotic theory. We hope that the meaning that Bong Joon-ho wants to convey can be interpreted well. This research was conducted by analyzing the data. The method used is a quantitative approach. The results of the study are discussed using a table that shows the Parasite film scene. The results showed that the film Parasite by Bong Joon-ho had 25 scenes which were analyzed using Pierce's semiotic theory which contained meaning about social inequality.